Effects of Kelulut honey from Trigona sp. on zebrafish (Danio rerio) embryo that mimics human embryonic development - Adenan, Mohd Noor Hidayat; Saiful Yazan, Latifah; Christianus, Annie; Md Hashim, Nur Fariesha; Harun, Abdul Rahim; Abdul Halim, Nur Hafizati; Sani, Mohd Zulmadi; Abdul Rahim, Khairuddin (Academic Journals, 2018)
Kelulut honey (KH) is a type of honey with various pharmacological properties that can be found in Malaysia. Nevertheless, the safety aspects of this honey have not been adequately addressed. This study evaluated the developmental toxicity of KH from Trigona sp on zebrafish (Danio rerio) embryos. Viable zebrafish embryos at 3 hours post fertilization (hpf) (early stage) and 24 hpf (organ development stage) were treated with KH (1 to 20 mg/mL). The embryos were examined for morphological abnormalities and viability until 96 h of KH treatment. Coagulated embryos were identified after treatment with KH (≥10 mg/mL) for 3 hpf group and KH (≥12 mg/mL) for 24 hpf group. The LC50 values of KH at 96 h of exposure for the 3 hpf and 24 hpf group were 12.52 and 16.36 mg/mL, respectively. The maximum allowable concentration (MAC) for KH on 3 hpf and 24 hpf group were 0.63 and 0.82 mg/mL, respectively. The irregular cardiac rate of the embryos was noted at 10 mg/mL for 3 hpf group and 13 mg/mL of KH for 24 hpf group. In summary, the early stage embryo (3 hpf group) was more sensitive to KH than the one of later stage (24 hpf group). It indicates that serious precautions should be taken into account in the use of any material including natural product, be it food or supplement, especially in the early stage of life.